2021
DOI: 10.1093/jimb/kuab014
|View full text |Cite
|
Sign up to set email alerts
|

Reduced viscosity mutants of Trichoderma reesei with improved industrial fermentation characteristics

Abstract: Morphological mutants of Trichoderma reesei were isolated following chemical or insertional mutagenesis. The mutant strains were shown to have reduced viscosity under industrially-relevant fermentation conditions and to have maintained high specific productivity of secreted protein. This allowed higher biomass concentration to be maintained during the production phase and, consequently, increased volumetric productivity of secreted protein. The causative mutations were traced to four individual genes (designat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Indeed, the key parameters such as pH, agitation, airflow, dissolved oxygen, temperature, and feeding pumps were affected by large-scale production of microbial mass production [16,18]. Many studies have been reported to evaluate the cultivation parameters for Trichoderma sp., by using a submerged fermentation system to increase its bioactive metabolites as well as conidia [14][15][16][17]. To detect perfect conditions for transposing the cultivation of endophytic T. harzianum to the industrial scale, the batch and exponential fedbatch fermentation modes were applied in our work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the key parameters such as pH, agitation, airflow, dissolved oxygen, temperature, and feeding pumps were affected by large-scale production of microbial mass production [16,18]. Many studies have been reported to evaluate the cultivation parameters for Trichoderma sp., by using a submerged fermentation system to increase its bioactive metabolites as well as conidia [14][15][16][17]. To detect perfect conditions for transposing the cultivation of endophytic T. harzianum to the industrial scale, the batch and exponential fedbatch fermentation modes were applied in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the tested microbial cells must survive multiple processing stages without destroying their quality and quantity [14]. Therefore, there are low-cost materials such as agro-wastes that have been utilized as carbon and nitrogen sources for culturing microbial cells to reduce production line costs [14][15][16][17]. For the commercial scale-up approach, two distinct fermentation systems called solid-state and submerged fermentation were applied accordingly to the sensitivity of microbial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most applications of the CRISPR‐Cas system also have direct utility and relevance with respect to Trichoderm a, for which CRISPR‐Cas can be applied to augment and/or enhance pre‐existing genetic engineering platforms (Liu et al, 2015). To date, researchers have constructed CRISPR‐Cas tools based on diversification strategies and have applied them to functional gene identification, strain modification, and other fields in T. reesei (Bodie et al, 2021; Chai et al, 2022; de Souza Maia Filho et al, 2017; Hao & Su, 2019; Li, Lin et al, 2021; Li, Liu et al, 2021; Liu et al, 2015; Rantasalo et al, 2019; Wu, Chen, Huang, et al, 2020; Wu, Chen, Qiu, et al, 2020; Zou, Bao et al, 2021; Zou, Li et al, 2021; Zou, Xiao et al, 2021). Nevertheless, some Trichoderma species, including T. harzianum (Vieira et al, 2021), T. atroviride (Primerano, 2021), and the unidentified species Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid viscosity affects the mixing process, mass transfer, and gas diffusion in the culture medium, and consequently, the Reynold number value, and correlates with the oxygen mass transfer coefficient [36,37]. In high-density microbiological cultures with a high biomass concentration, the culture liquid turns viscous, which significantly influences hydrodynamics, heat and mass transfer, cell growth kinetics, and formation and accumulation of secondary metabolites in the culture medium [38][39][40]. It is believed that the increase in culture medium viscosity observed in the microorganism-mediated processes, including Schizochytrium sp., is largely due to the production of extracellular polymeric substances (EPS) [41,42].…”
Section: Introductionmentioning
confidence: 99%